RELATIONSHIP BETWEEN WORK POSTURE AND REPETITIVE MOVEMENTS WITH COMPLAINTS OF CARPAL TUNNEL SYNDROME (CTS) ON STONE-BREAKING WORKERS ON THE BANKS OF THE KALISETAIL RIVER. SETAIL VILLAGE, GENTENG DISTRICT, BANYUWANGI REGENCY - Kumalasari, Ulviana Dewi; Dwiyanti, Endang (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACT Background: Workers who perform repetitive movements and work in a manner that remains seated for a long time experience Carpal Tunnel Syndrome in stone-breaking workers. It can reduce worker productivity because CTS can cause disability. Objective: Analyzing the relationship between work posture and repetitive movements with Carpal Tunnel Syndrome in stone-breaking workers on the banks of the Kalisetail River, Genteng District, Banyuwangi Regency. Method: This study was included in an observational analytic study with a cross-sectional research design. The samples in this study were all stone-breaking workers, consisting of 30 people, along the Kalisetail River, Setail Village, Genteng District, and Banyuwangi Regency. Results: The results showed the relationship between work posture (r = 0.420) and repetitive movement (r = 0.671) with complaints of Carpal Tunnel Syndrome in stone-breaking workers on the banks of the Kalisetail River was sufficient or moderate until strong. Conclusion: This study concludes that the relationship between work posture and repetitive movements of Carpal Tunnel Syndrome was sufficient until strong in stone-breaking workers on the outskirts of Kalisetail River. The researcher suggests applying rest breaks or recovery times, physical exercise during break times, and workplace adjustment. ABSTRAK Latar Belakang: Pekerja yang melakukan gerakan repetitif dan bekerja dengan posisi tetap yaitu duduk dalam waktu yang lama merupakan penyebab terjadinya Carpal Tunnel Syndrome pada pekerja pemecah batu. Hal ini dapat menurunkan produktivitas pekerja karena CTS dapat menimbulkan kecacatan. Tujuan: Menganalisis hubungan antara postur kerja dan gerakan repetitif dengan Carpal Tunnel Syndrome pada pekerja pemecah batu di pinggiran Sungai Kalisetail Kecamatan Genteng Kabupaten Banyuwangi. Metode: Penelitian ini termasuk dalam penelitian analitik observasional dengan desain penelitian cross sectional. Sampel dalam penelitian ini adalah semua populasi pekerja pemecah batu di sepanjang Sungai Kalisetail Desa Setail, Kecamatan Genteng, Kabupaten Banyuwangi sebanyak 30 orang. Hasil: Hasil penelitian menunjukkan bahwa hubungan antara postur kerja (r=0,420 dan gerakan repetitif (r=0,671) dengan keluhan Carpal Tunnel Syndrome pada pekerja pemecah batu di pinggiran Sungai Kalisetail adalah cukup atau sedang sampai kuat. Kesimpulan dari penelitian ini adalah hubungan antara postur kerja dan gerakan repetitif dengan keluhan Carpal Tunnel Syndrome adalah cukup atau sedang sampai kuat pada pekerja pemecah batu di pinggiran Sungai Kalisetail Kecamatan Genteng Kabupaten Banyuwangi. Saran peneliti adalah penerapan jeda istirahat atau waktu pemulihan, latihan fisik di sela waktu istirahat, dan penyesuaian tempat kerja.